1987
DOI: 10.1113/jphysiol.1987.sp016408
|View full text |Cite
|
Sign up to set email alerts
|

Effects of caffeine on intracellular calcium concentrations in frog skeletal muscle fibres.

Abstract: 1. The mechanism of twitch potentiation by caffeine was studied in single muscle fibres dissected from m. tibialis anterior of Rana temporaria. Fibres were injected with a Ca2+-sensitive photo-protein, aequorin, and the resultant light signal and tension were simultaneously recorded. 2. In twitch responses triggered every 60 s, peaks of light and tension were maintained at a constant level. Low concentrations of caffeine (0.2-0.4 mM) potentiated twitch tension accompanied by a slight increase in light signal. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
39
0

Year Published

1992
1992
1995
1995

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 28 publications
(32 reference statements)
3
39
0
Order By: Relevance
“…Our results confirm earlier reports that caffeine increases tetanic force, increases [Ca2+]i during the tetanus and slows the rate of relaxation (Pagala, 1980;Konishi & Kurihara, 1987;Fryer & Neering, 1989 Wendt & Stephenson (1983) in skinned extensor digitorum longus fibres from rat. They showed that 5 mm caffeine produced a 0f06 log unit shift in Ca50 which compares with our observed 0-13 shift.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Our results confirm earlier reports that caffeine increases tetanic force, increases [Ca2+]i during the tetanus and slows the rate of relaxation (Pagala, 1980;Konishi & Kurihara, 1987;Fryer & Neering, 1989 Wendt & Stephenson (1983) in skinned extensor digitorum longus fibres from rat. They showed that 5 mm caffeine produced a 0f06 log unit shift in Ca50 which compares with our observed 0-13 shift.…”
Section: Discussionsupporting
confidence: 82%
“…(2) Alternatively, caffeine might slow the release and/or uptake of Ca2+. There is already considerable evidence for this possibility as the time course of decline of [Ca2+]i has been shown to slow in the presence of caffeine (Konishi & Kurihara, 1987;Fryer & Neering, 1989; Simon, Klein & Schneider, 1989). …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Procaine in the millimolar range competitively inhibited caffeine contractures (Feinstein, 1963). The addition of 0-5-0-8 mM-procaine to fibres treated with 0-6 mM-caffeine inhibited the rise of resting glow induced by caffeine alone, but potentiated the peak of light and the peak of tension during a twitch (Konishi & Kurihara, 1987). The potentiated twitch response in these experiments could again be due to a prolongation of the action potential in the presence of procaine (Inoue & Frank, 1962 The present experiments involving brief (10-30 ms) depolarizations clearly indicate a specific inhibitory effect of procaine on the CICR induced by caffeine.…”
Section: Discussionmentioning
confidence: 99%
“…In amphibian skeletal muscle fibers, a cell type in which [Ca2+]i has been studied most extensively, the quantification of resting [Ca2+]i has been attempted with various methods, including Ca2+-sensitive microelectrodes (Tsien and Rink, 1980;Coray, Fly, Hess, McGuigan, and Weingart, 1980;Lopez, Alamo, Caputo, Dipolo, and Vergara, 1983;Weingart and Hess, 1984;Blatter and Blinks, 1991); aequorin (Blinks, Wier, and Snowdowne, 1980;Konishi and Kurihara, 1987;Blatter and Blinks, 1991); and tetracarboxylate indicators such as fura-2 (Klein, Simon, Szucs, and Schneider, 1988;Suda and Kurihara, 1991), fura red , and fluo-3 (Harldns, Kurebayashi, and Baylor, 1993). However, methodological difficulties encountered in the above studies make the quantification of [Ca~+]i somewhat uncertain, and consequently the estimated values for the resting [Ca~+]i vary widely.…”
Section: Introductionmentioning
confidence: 99%